PENGEMBANGAN KATALOG BERBASIS QR-CODE TUMBUHAN FAMILI EUPHORBIACEAE DI KAWASAN KONSERVASI - Yohana Tari Buku; Riantina Fitra Aldya; Yuni Pantiwati (Universitas Tribhuwana Tunggadewi, 2023)
This study aims to determine the feasibility of developing QR-Code-based catalogs, especially in the plant group of the Euphorbiaceae family. This research was an RD development research with the ADDIE method. This research included the analysis stage to assess the needs of the P-WEC conservation area, followed by the design stage to design a QR-Code-based catalog, then the development stage to create products in the form of QR-Code-based catalogs, especially for the plant group of the Euphorbiaceae family continued with validation by media experts and material experts and ended with the implementation phase in the form of a trial of catalog assessment by 20 visitors to the P-WEC conservation area. The results showed that based on the results of validation by media experts, they scored 4.17 and based on validation by material experts, they scored 3.95 with each having a decent category, then the trial results got a value of 4.16 with a decent category. QR-Code-based catalog development can be used because it has benefits in the form of efficiency because it prevents visitors from wasting time on search engines and being exposed to irrelevant information, this catalog can be accessed by mobile devices independently by visitors using a scanner application on Android to find out the variety and benefits of the Euphorbiaceae plant group.